2004
DOI: 10.1007/s00253-004-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineered biosynthesis of 16-membered macrolides that require methoxymalonyl-ACP precursors in Streptomyces fradiae

Abstract: Development of host microorganisms for heterologous expression of polyketide synthases (PKS) that possess the intrinsic capacity to overproduce polyketides with a broad spectrum of precursors supports the current demand for new tools to create novel chemical structures by combinatorial engineering of modular and other classes of PKS. Streptomyces fradiae is an ideal host for development of generic polyketide-overproducing strains because it contains three of the most common precursors--malonyl-CoA, methylmalon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Researchers are now focusing on PPTs within alternative heterologous hosts, such as Pseudomonas (16) and Streptomyces (20,40) species. The ability to distinguish between the Sfp-like PPT subfamilies and the likelihood of association with either PK or NRPS biosynthetic pathways has important implications in heterologous expression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are now focusing on PPTs within alternative heterologous hosts, such as Pseudomonas (16) and Streptomyces (20,40) species. The ability to distinguish between the Sfp-like PPT subfamilies and the likelihood of association with either PK or NRPS biosynthetic pathways has important implications in heterologous expression.…”
Section: Discussionmentioning
confidence: 99%
“…and Streptomyces spp. (22,36), are being investigated for heterologous expression and biochemical characterization of secondary metabolite gene clusters from cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Floss et al (7) subsequently showed that during ansamitosin biosynthesis, O-methylation occurs before incorporation by the PKS; therefore, MM-ACP is the in vivo extender unit, not HM-ACP. Whereas genetic experiments support the hypothesis that these enzymes are involved in the incorporation of a MM-ACP extender unit (7,10,11) and a crystal structure of FkbI has been determined (9), biochemical evidence for MM-ACP has yet to be provided.…”
mentioning
confidence: 99%